2014
DOI: 10.3389/fimmu.2014.00632
|View full text |Cite
|
Sign up to set email alerts
|

Histological Analysis of γδ T Lymphocytes Infiltrating Human Triple-Negative Breast Carcinomas

Abstract: Breast cancer is the leading cause of cancer death in women and the second most common cancer worldwide after lung cancer. The remarkable heterogeneity of breast cancers influences numerous diagnostic, therapeutic, and prognostic factors. Triple-negative breast carcinomas (TNBCs) lack expression of HER2 and the estrogen and progesterone receptors and often contain lymphocytic infiltrates. Most of TNBCs are invasive ductal carcinomas (IDCs) with poor prognosis, whereas prognostically more favorable subtypes suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…γδ T cells infiltrate a variety of cancers and modulate anti-tumor immunity [41][42][43][44], and a recent extensive gene expression study identified tumor-infiltrating γδ T cells as the most favorable prognostic marker in many types of cancer [45]. Along with their unique beneficial features such as the production of abundant pro-inflammatory cytokines, including IFN-γ and TNF-α, MHC-independent recognition of antigens, direct lysis of tumor cells, antibody-dependent cellular cytotoxicity (ADCC), and antigen presentation capacity [46], γδ T cells are proposed to constitute a promising target in cancer immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…γδ T cells infiltrate a variety of cancers and modulate anti-tumor immunity [41][42][43][44], and a recent extensive gene expression study identified tumor-infiltrating γδ T cells as the most favorable prognostic marker in many types of cancer [45]. Along with their unique beneficial features such as the production of abundant pro-inflammatory cytokines, including IFN-γ and TNF-α, MHC-independent recognition of antigens, direct lysis of tumor cells, antibody-dependent cellular cytotoxicity (ADCC), and antigen presentation capacity [46], γδ T cells are proposed to constitute a promising target in cancer immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In a small study, which focussed on triple negative breast cancer, Hidalgo and coworkers demonstrated that the lymphocytic infiltrate of these tumours contained many γδT lymphocytes, compared to normal breast tissue. They compared ductal and medullary breast cancer tissue and found differences in the distribution of γδT lymphocytes between the two tumour types; they were more frequently located in the stroma of the ductal specimens whereas they were more typically located in the tumour parenchyma and at the invasive tumour cell margin of medullary tumours (42). independent of receptor status, and improved overall survival in the HER2 positive subtype (HR 0.27; 95% CI:0.10-0.73; p=0.009).…”
Section: γδT Lymphocytes In Breast Cancer -Human Studiesmentioning
confidence: 99%
“…3 Recently, the important biological role of gdT cells in cancer immune surveillance has been further highlighted by the fact that gdT cells infiltrate various tumors. 4,5 However, the biological understanding of cancer immune surveillance and potential clinical applicability of gdT cells, or their individual receptors, is substantially hampered by the lack of well-defined gdT-cell receptor (TCR) ligands, as well as their precise molecular requirements for recognition. 6 gdT-cell ligands that have been identified so far are mostly associated with metabolic changes in stressed cells.…”
Section: Introductionmentioning
confidence: 99%